2012
DOI: 10.2174/138920012803762684
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Lysosomes

Abstract: Lysosomes are cytoplasmic organelles delimited by a single membrane and filled with a variety of hydrolytic enzymes active at acidic pH and collectively capable to degrade the vast majority of macromolecules entering lysosomes via endocytosis, phagocytosis or autophagy. In this review, we describe the lipid composition and the dynamic properties of lysosomal membrane, the main delivery pathways of lipids to lysosomes and their catabolism inside lysosomes. Then, we present the consequences of a lipid accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 354 publications
0
15
0
8
Order By: Relevance
“…EE and LE exhibit differences in their protein and lipid composition, which reflect their different functions (Falguières et al ., ). The inner leaflet of the limiting membranes from early/recycling endosomes, are rich in SM, Cho, glycospingolipids and glycerophospholipids whereas those from LE/Lys contain a higher proportion of PC, lysobiphosphatidic acid (LBPA) and ceramide (Cer), as well as less phosphatidylserine (PS) and SM than those from EE (Hammer et al ., ). There are detergent‐resistant membrane domains on the cytosolic face of all endosomal compartments (Scita and Di Fiore, ; Pálfy et al ., ), and these domains serve as platforms for docking and assembly of signalling complexes, as occurs in the cytosolic leaflet of the PM (Scita and Di Fiore, ; Pálfy et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…EE and LE exhibit differences in their protein and lipid composition, which reflect their different functions (Falguières et al ., ). The inner leaflet of the limiting membranes from early/recycling endosomes, are rich in SM, Cho, glycospingolipids and glycerophospholipids whereas those from LE/Lys contain a higher proportion of PC, lysobiphosphatidic acid (LBPA) and ceramide (Cer), as well as less phosphatidylserine (PS) and SM than those from EE (Hammer et al ., ). There are detergent‐resistant membrane domains on the cytosolic face of all endosomal compartments (Scita and Di Fiore, ; Pálfy et al ., ), and these domains serve as platforms for docking and assembly of signalling complexes, as occurs in the cytosolic leaflet of the PM (Scita and Di Fiore, ; Pálfy et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…[74][75][76] during which they are exposed to varying conditions, such as pH changes from 7.4 (in the extracellular medium), to 5.5 (in late endosomes), and finally to 4.5 (in lysosomes). 77 This altered environment can have several consequences, for example it was shown that bound or adsorbed proteins can be rapidly degraded. 78 Ag NPs, some of the most widely studied engineered NPs, were shown to dissolve in endosomes and lysosomes.…”
Section: Colloidal Interactions In Cell Culture Mediummentioning
confidence: 99%
“…Since lysosomes are the final destination for autophagy and other endocytotic pathways , endo/lysosomal dysfunction not only affects macroautophagy but also impairs CMA, recycling of membrane lipids, sorting of lipids and lipoproteins into appropriate intracellular compartments, and promotes lipotoxic cell death (23,154,155).…”
Section: Regulation Of Lysosomal Function By Lipidsmentioning
confidence: 99%